Technoeconomic Environmental and Risk Analysis of Marine Gas Turbine Power Plants - Tsoudis, Evangelos (Cranfield University, 2008)
A novel generic Technoeconomic, Environmental and Risk Analysis (TERA) computational method was developed for marine power plants that are composed of existing or at preliminary design stage marine gas turbines. The method is composed of several numerical models in order to realistically approach the life cycle operation of a marine gas turbine power plant-according to the operational profile of the platform marine vessel type-coupled to an integrated full electric propulsion system and stochastically estimate the power plant’s life cycle net present cost. The development of the TERA method led to the creation of an integrated computational marine vessel operation environment which was given the name “Poseidon”. The performance and exhaust emissions (nitric oxide, carbon monoxide, carbon dioxide and unburned hydrocarbon) of five 25 Megawatt marine gas turbines of the same technology level and design-point overhaul interval were simulated and modelled in “Poseidon”. The exhaust emissions of the modelled gas turbines were calibrated for two combustor technologies: conventional and dry-low emissions for both distillate fuel and natural gas used as fuel. The marine gas turbines are: existing simple cycle, novel twin-mode intercooled cycle, fictional intercooled cycle, fictional recuperated cycle and partly based on an existing design, intercooled/recuperated cycle. Three marine vessel types that require the same power plant output power and configuration but they utilise different operational profiles were also realistically modelled. The marine vessels are: Destroyer, RoPax fast ferry and LNG carrier. It was assumed that the Destroyer’s and RoPax fast ferry’s power plants use distillates fuel and the LNG carrier’s power plant uses compressed natural gas as fuel. Three case studies defined by each of the marine vessels were performed in order to investigate the economic feasibility of the advanced cycle gas turbine power plants in comparison with the power plant composed by existing gas turbines, in a possible future scenario were all four modelled exhaust emission quantities are accurately measured and taxed. The investment on dry-low emissions combustor technology was also investigated as part of each case study. Both technical and economic input datasets are realistic. Due to time restrains the LNG carrier case study features only the intercooled/recuperated gas turbine power plant. Obtained results are presented and discussed separately for each case study.